The Effect of Training and Work Professionalism on the Performance of Soldiers and Civil Servants at the TNI Historical Center - Sugiarti, Sugiarti; Widodo, Sri (Dinasti International Journal of Management Science, 2025)
The research objectives are as follows to determine whether together the influence of Training and Work Professionalism on the Performance of Soldiers and Civil Servants at the TNI Historical Center. The sampling technique used in this study the author used Total Sampling technique or randomly All soldiers are the population and sampled as a whole. Based on the results of multiple correlation tests, it is known that the magnitude of the relationship between Training (X1), Work Professionalism (X2) simultaneously on the Performance of Soldiers and Civil Servants (Y) calculated by the correlation coefficient is 0.962. This shows a very strong influence. While simultaneously the contribution or contribution of the variables Training (X1), Work Professionalism (X2) to the Performance of Soldiers and Civil Servants (Y) is 92.6% while 7.4% is determined by other variables, not examined in this study. The intercept constant value of 42.983 can be defined that if the Training (X1), Work Professionalism (X2) variable increases by 1 unit, the Soldier and Civil Servant Performance (Y) variable will increase by 42.983. It can also be defined that the intercept constant value of 42.983 describes the performance of Soldiers and Civil Servants (Y) on average if the variables Training (X1) and Work Professionalism (X2) are 0 (zero).